Design Criteria Of Performance Management System Using Balanced Scorecard And Analytic Hierarchy Process (case Study Pt. Duta Harapan Tunggal) - Muhammad Firhand Aswad; Budi Sulistyo; Budhi Yogaswara (eProceedings of Engineering, 2018)
Abstract PT. Duta Harapan Tunggal is a company engaged in the production of beverages. This company employed performs a financial aspect to evaluate company’s performance. However, this is unable to control the company’s operational process,customers, and learning and growth. Therefore, it is necessary to create a measurement tool that is in line with the vision and mission of the company. This study aims to develop a balanced scorecard to measure the company’s performance. The final result of this final project is determine the strategies based on the company’s vission and mission, to determine the performance indicators. The weighting of each indicator for financial perspective is 26%, customer perspective is 44%, internal business process perspective is 15%, learning and growth perspective is 14%. The highest weighting score is the customer perspective. Keywords – Balanced Scorecard (BSC), Analytical Hierarchy Process (AHP), Performance Management